The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s12887-021-02713-0
|View full text |Cite
|
Sign up to set email alerts
|

Minimum acceptable diet among children aged 6–23 months in South Kivu, Democratic Republic of Congo: a community-based cross-sectional study

Abstract: Background Suboptimal child nutrition remains the main factor underlying child undernutrition in Democratic Republic of Congo (DRC). This study aimed to assess the prevalence of minimum acceptable diet and associated factors among children aged 6–23 months old. Methods Community-based cross-sectional study including 742 mothers with children aged 6–23 months old was conducted in 2 Health Zones of South Kivu, Eastern DRC. WHO indicators of Infant an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
17
4
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 33 publications
11
17
4
2
Order By: Relevance
“…The likelihood of receiving the recommended minimum acceptable diet was higher among urban residents compared to those who reside in rural areas. This finding was in line with studies from South Kivu, the Democratic Republic of Congo [ 46 ], and Ethiopia [ 52 ]. This might be due to information access.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The likelihood of receiving the recommended minimum acceptable diet was higher among urban residents compared to those who reside in rural areas. This finding was in line with studies from South Kivu, the Democratic Republic of Congo [ 46 ], and Ethiopia [ 52 ]. This might be due to information access.…”
Section: Discussionsupporting
confidence: 92%
“…The current study also pointed out that infants and children of households with medium and highest wealth indexes were more likely to receive the minimum acceptable diet compared to those with the lowest wealth index. This finding was similar to studies conducted in South Kivu, Democratic Republic of Congo [ 46 ], Philippines [ 49 ], and Goncha district, north West Ethiopia [ 48 ]. This may be due to the fact that diversifying diet and frequent feeding relies on the income of the households to secure their diet, which may be a difficulty for low-income countries like Ethiopia.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Additionally, in our cohort, 30% of children did not consume an protein source within the past 24 h. Country‐level DHS data from DRC found that 17% of children 6–23 months of age achieved MDD, even lower than the 26% in our study area (Heidkamp et al, 2020 ). A recently published study from South Kivu, DRC found that 21% of children 6–23 months in rural areas achieved MDD, and 45% of children in urban areas (Kambale et al, 2021 ). This is the only other published study on MDD from South, Kivu, DRC, and is similar to the findings from our study.…”
Section: Discussionmentioning
confidence: 99%